Reaktualisasi & Revitalisasi Sumber Penerimaan Negara - Dedi Junaedi; Faisal Salistia (Reslaj : Religion Education Social Laa Roiba Journal, 2019)
The purpose of this study is to actualize and revitalize fiscal concepts or sources of revenue in Indonesia in a perspective review of Islamic economic thought. The method used is the study of literature and qualitative descriptive analysis of thoughts that have developed in the history of Islamic economic thought as well as its adaptation, actualization, revitalization and contextualization efforts to formulate more stable, blessing and sustainable sources of Indonesia's APBN revenue. The results of the study can be briefly formulated that in general fiscal policy discusses the role of the state in the function of allocation, distribution and stabilization of the national economy. In the allocation function, the state determines what state financial resources are used for; the distribution function regulates how state policies manage the budget (expenditure) to create a mechanism of equitable economic distribution in society; and the function of stabilization is how the state creates a stable and sturdy economy that supports the economic wheels. The budget deficit - as experienced by many countries, including Indonesia - is a signal of the importance of managing a country's fiscal policy. The history of the glory of Islam has provided valuable lessons on how Islamic economic development was once a solution that delivered prosperity and prosperity to all its people. Various sources of revenue ranging from zakat, ghanimah, fai, kharaj, fai, ushr, khumus, nawaib, amwal fadla, special taxes, import duties, import duties, grants, gifts, expiation, and several other financial sanctions have been moved to become a source of state revenue very big one. If you are willing and willing to make efforts to adapt, re-actualize and revitalize the sources of revenue, a similar succession can be applied at the present time by any country, including Indonesia. Keywords: budget, Islamic economics, financial, fiscal, tax, zakat